A case report: uterine fibroids treated by polyvinyl alcohol particles - Tonpe, Sudhanshu; Warbhe, Himandri Harish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine fibroids, the most common type of tumor among women of reproductive age, are associated with heavy menstrual bleeding, sub-fertility, abdominal discomfort, and a reduced quality of life. For women who wish to preserve their uterus and who have not had a response to medical treatment, uterine artery embolization and myomectomy are therapeutic options. A 35-year-old asthmatic female came to our hospital with dysfunctional uterine bleeding (DUB) from the past 6 months complicated by severe anemia requiring multiple blood transfusions. Ultrasound of the pelvis shows a bulky uterus with an intramural fundal fibroid indenting the endometrial cavity with fluid collection within. Considering the age and reduced Hemoglobin and the co-morbidity of asthma, endovascular PVA (Polyvinyl alcohol particle) particle embolization of both uterine arteries was performed. Post procedure, there was there were no acute symptoms. Six months after the intervention, the patient’s pelvic USG shows significant reduction in the size of the fundal fibroid with total absence of menstrual bleeding. Therefore, endovascular uterine artery embolization with PVA particles is safe and effective method to treat DUB.